1999
DOI: 10.1182/blood.v93.5.1684
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Receptor for Hyaluronan-Mediated Motility (RHAMM) Characterizes the Malignant Clone in Multiple Myeloma: Identification of Three Distinct RHAMM Variants

Abstract: The receptor for hyaluronan (HA)-mediated motility (RHAMM) controls motility by malignant cells in myeloma and is abnormally expressed on the surface of most malignant B and plasma cells in blood or bone marrow (BM) of patients with multiple myeloma (MM). RHAMM cDNA was cloned and sequenced from the malignant B and plasma cells comprising the myeloma B lineage hierarchy. Three distinct RHAMM gene products, RHAMMFL, RHAMM−48, and RHAMM−147, were cloned from MM B and plasma cells. RHAMMFL was 99% homologous to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…RHAMM forms with apparent molecular weights (Mr) less than 82 kDa may arise by alternate splicing of RHAMM mRNA (Hall et al, 1995; Assman et al, 1999; Crainie et al, 1999), although we found no evidence for RHAMM splice variants in rat brain (unpublished observations). Those forms with Mr greater than predicted from RHAMM cDNA sequence likely arise from posttranslational modifications, either alone or in concert with alternate splicing, that influence migration rates on SDS‐PAGE gels.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…RHAMM forms with apparent molecular weights (Mr) less than 82 kDa may arise by alternate splicing of RHAMM mRNA (Hall et al, 1995; Assman et al, 1999; Crainie et al, 1999), although we found no evidence for RHAMM splice variants in rat brain (unpublished observations). Those forms with Mr greater than predicted from RHAMM cDNA sequence likely arise from posttranslational modifications, either alone or in concert with alternate splicing, that influence migration rates on SDS‐PAGE gels.…”
Section: Discussionmentioning
confidence: 42%
“…Overexpression of RHAMM was reported to increase cell migration, and mutant RHAMM lacking HA binding domains abrogated this motile response (Hall et al, 1995). Several RHAMM isoforms have been identified, and some of these appear to be generated by alternative splicing of RHAMM mRNA (Entwistle et al, 1995; Assmann et al, 1999; Crainie et al, 1999). Participation of RHAMM in cell signaling was suggested by its involvement in events leading to phosphorylation of erk1/2, paxillin, and focal adhesion kinase (Hall et al, 1994; Lokeshwar and Selzer, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Alternate splicing of RHAMM has been reported in other systems, including B cells of the multiple myeloma lineage and HeLa cells (Crainie et al, 1999; Assmann et al, 1999). By using PCR primers flanking alternatively spliced sequence (primer pair 6; Table 1), we were able to confirm the presence of RHAMM alternate splicing in HeLa cells (not shown).…”
Section: Resultsmentioning
confidence: 84%
“…These results suggest that Rhamm has both extracellular and intracellular functions. However, the role of Rhamm as a cell surface HA receptor became controversial partly because cloning of the human (Wang et al, 1996;Hofmann et al, 1998;Crainie et al, 1999) and mouse genes (Hofmann et al, 1998) revealed an absence of both a signal peptide required for export through the Golgi/ER and membrane spanning domains common to most cell surface receptors. We now know that Rhamm resembles a group of intracellular proteins that also lack these signature characteristics of classical cell surface proteins but that are nevertheless found Rhamm −/− fi broblasts are defective in CD44-mediated ERK1,2 motogenic signaling, leading to defective skin wound repair R hamm (receptor for hyaluronan-mediated motility) is an hyaluronan binding protein with limited expression in normal tissues and high expression in advanced cancers.…”
Section: Introductionmentioning
confidence: 99%